2008
DOI: 10.1111/j.1467-9787.2008.00582.x
|View full text |Cite
|
Sign up to set email alerts
|

OLS ESTIMATION AND THE t TEST REVISITED IN RANK‐SIZE RULE REGRESSION*

Abstract: The rank-size rule and Zipf's law for city sizes have been traditionally examined by means of OLS estimation and the t test. This paper studies the accurate and approximate properties of the OLS estimator and obtains the distribution of the t statistic under the assumption of Zipf's law (i.e., Pareto distribution). Indeed, we show that the t statistic explodes asymptotically even under the null, indicating that a mechanical application of the t test yields a serious type I error. To overcome this problem, crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 19 publications
(43 reference statements)
1
23
0
Order By: Relevance
“…For a zipfian urban system, the slope α should be practically equal to ‐1; in this case we say that the rank‐size rule is validated. The t ‐test is used to decide if the value of the exponent α is equal to ‐1 or not (Nishiyama et al ., , p. 692).…”
Section: Zipf's Lawmentioning
confidence: 97%
“…For a zipfian urban system, the slope α should be practically equal to ‐1; in this case we say that the rank‐size rule is validated. The t ‐test is used to decide if the value of the exponent α is equal to ‐1 or not (Nishiyama et al ., , p. 692).…”
Section: Zipf's Lawmentioning
confidence: 97%
“…The main problem is that the maximum likelihood (ML) estimator is more efficient if the underlying stochastic process is really a Pareto distribution (Gabaix & Ioannides, 2004;Goldstein, Morris, & Yen, 2004). Furthermore, as Gabaix and Ioannides (2004), Nishiyama, Osada, and Sato (2008), and Clauset et al (2009) emphasize, the estimates of the Pareto exponent are subject to systematic and potentially large errors. Finally, Gabaix and Ibragimov (2011) point out that this procedure is strongly biased in small samples.…”
Section: City Size Distributionmentioning
confidence: 99%
“…Given these estimates, evidence against Zipf's law is then assessed by testing if an estimated slope coefficient is significantly different from −1. However, it has been shown that the OLS estimate of β j in and its associated standard error are biased downward, with the bias diminishing as the number of observational units ( M ) increases (Gabaix and Ioannides, 2004; Nishiyama and Osada, 2004; Nishiyama, Osada, and Sato, 2008). Hence, failure to correct for these biases means one would more often reject Zipf's law when it is in fact true.…”
Section: Empirical Analysismentioning
confidence: 99%